Research Evolution, Hot Topics, and Prospects of Wuqinxi: A Visual Analysis Based on CiteSpace (Journal of humanities and social sciences exploratio, 2026)
Wuqinxi (Five-Animal Exercises) serves as an important vehicle for the preservation, innovation, and dissemination of China’s outstanding traditional culture. Using CiteSpace software, this study conducts a visual analysis of 944 Wuqinxi-related articles indexed in the China National Knowledge Infrastructure (CNKI) to explore research progress and hotspots in the field. The findings show a generally increasing trend in the number of published studies on Wuqinxi. A research team centered around Yu Dinghai has emerged as a core group in the field, with institutions such as Anhui University of Chinese Medicine and Shanghai University of Sport contributing substantial research output; however, inter-institutional collaboration remains to be strengthened. The evolution of research in this area can be divided into three stages: an initial exploratory stage (1978–2007), a stage of rapid development (2008–2021), and a stage of deepening development (2022 to present). Research hotspots mainly cluster around three major themes: historical origins and cultural connotations, inheritance and development, and promotion and dissemination. The research content remains relatively narrow in scope. Future studies should expand the spatial scope of research and deepen the integration of Wuqinxi with practical social needs, cutting-edge technologies, and related disciplines.
Keywords: Wuqinxi; CiteSpace; Research trends; Visualization